Enhancing Thai EFL Students’ EFL Vocabulary Knowledge through the Use of Task-Based Language Teaching and Storytelling Technique Adopting Thai Folktales - Tachom, Khomkrit (Asian Journal of Education and Training, 2021)
This study aimed to examine the development of EFL students’ vocabulary knowledge adopting a task-based method with 32 Thai students who enrolled in an English for Communication course at a university in northern Thailand. This study emphasized improving the Thai EFL students’ English vocabulary knowledge by requiring students to retell six Thai folktales in English translation to their group members. The pretest-posttest design, as well as an interview, were employed to indicate the students’ vocabulary improvement after retelling Thai folktales. The findings showed that the students’ post-test scores were statistically higher than their pre-test scores, and the students felt that the folktale tasks helped them enhance their vocabulary knowledge. The results of this study indicate that the students learned English vocabulary in an engaging and meaningful way through storytelling; therefore, the students’ vocabulary retention is likely high.